Competitive electroformation of silver and oxygen overlayers on polycrystalline rhodium in acid - Parajón Costa, Beatriz Susana (1988)
In the present work results obtained for Ag deposition on polycrystalline Rh in H2SO4 + Ag2SO4 solutions are reported. This system offers a relatively wide potential range where both reactions, namely, the UPD of Ag and O-electrodesorption can be studied either simultaneously or independently.